Pengaruh Locus of Control, Performance, Turnover Intentions, dan Organizational Commitment Terhadap Perilaku Disfungsional Audit - Fitri; Herawansyah; Danang Adi Saputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the influence of locus of control, performance, turnover intention, and organizational commitment on dysfunctional auditor behavior in public accounting firms in Bengkulu. The research method used was quantitative with a descriptive approach, and primary data was collected through questionnaires distributed to auditors in Bengkulu. The sample used was 97 respondents. Data analysis shows that locus of control has no influence on dysfunctional audits. However, organizational performance and commitment have a significant influence on dysfunctional audit behavior. Meanwhile, turnover intention has a negative and significant effect on dysfunctional audits. This finding is important for maintaining public trust in the audit profession. High auditor performance is related to low dysfunctional behavior, while high turnover intention is not related to dysfunctional behavior that impacts audit quality. Organizational commitment also plays an important role in reducing dysfunctional auditor behavior. This research contributes to the understanding and handling of problems related to dysfunctional behavior in the audit profession.